"We Hardly Ever Talk about It": Emotional Responsive Attunement in Couples after a Child's Death. Issue 1 (5th January 2017) - Hooghe, An; Rosenblatt, Paul C.; Rober, Peter
Abstract : Within Western cultural traditions, the idea that parents should talk about the death of their child with each other is deeply rooted. However, across bereaved parent couples there are wide variations in communication about their grief with each other. In this study, we explored the experiences of bereaved couples related to the process of talking and not talking. We used a thematic coding approach to analyze 20 interviews with 26 bereaved parents (11 interviewed as couples, four as individuals). Four main meanings emerged out of our analysis: not talking because of the inadequacy and pointlessness of words in grief, not talking as a way to regulate emotions in daily life, not talking as an expression of a personal, intimate process, and not talking because the partner has the same loss but a different grief process. In addition, we found that the process of talking and not talking can partly be understood as an emotional responsive process on an intrapersonal and interpersonal level. In this process partners search for a bearable distance from their own grief and their partner's, and attune with their relational context. A better understanding of this process is sought in a dialectical approach, emphasizing the value of both talking and not talking in a tense relationship with each other. Implications for clinical work are described. Abstract : Video Abstract